2016
DOI: 10.17352/2455-5363.000010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B, Hepatitis C, HIV and Malaria Co Infection among Patients Infected with Visceral Leishmaniasis in Gedarif, Eastern Sudan

Abstract: Background: Concomitant infections with HBV,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Thus, a total of seven studies [ 20 26 ] remained and were included in the systematic review and meta-analysis. An additional three studies [ 27 29 ], identified through the review of reference lists of the included studies, and two studies [ 30 , 31 ] identified from Google Scholar, were also included, resulting in a overall total of 12 studies [ 20 31 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a total of seven studies [ 20 26 ] remained and were included in the systematic review and meta-analysis. An additional three studies [ 27 29 ], identified through the review of reference lists of the included studies, and two studies [ 30 , 31 ] identified from Google Scholar, were also included, resulting in a overall total of 12 studies [ 20 31 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies identified Plasmodium infection using microscopy or a rapid diagnostic test (RDT). For the identification of VL infection, four of the included studies used immuno-chromatographic techniques (ICTs) or RDTs [ 20 , 24 , 27 , 28 ]; three studies used ICTs, microscopic examination and direct agglutination tests (DATs) [ 25 , 26 , 29 ]; three studies used DATs and microscopy [ 21 , 30 , 31 ]; and one study used DATs and bone marrow aspiration (smear and culture) [ 22 ]. The presence of anemia and malnutrition at admission in patients with co-infection and those with VL was reported in three studies [ 25 , 26 , 30 ] (Additional file 2 : Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations